Regulation of cortical actin cytoskeleton assembly during polarized cell growth in budding yeast (The Rockefeller University Press, 1995)
We have established an in vitro assay for assembly of the cortical actin cytoskeleton of budding yeast cells. After permeabilization of yeast by a novel procedure designed to maintain the spatial organization of cellular constituents, exogenously added fluorescently labeled actin monomers assemble into distinct structures in a pattern that is similar to the cortical actin distribution in vivo. Actin assembly in the bud of small-budded cells requires a nucleation activity provided by protein factors that appear to be distinct from the barbed ends of endogenous actin filaments. This nucleation activity is lost in cells that lack either Sla1 or Sla2, proteins previously implicated in cortical actin cytoskeleton function, suggesting a possible role for these proteins in the nucleation reaction. The rate and the extent of actin assembly in the bud are increased in permeabilized delta cap2 cells, providing evidence that capping protein regulates the ability of the barbed ends of actin filaments to grow in yeast cells. Actin incorporation in the bud can be stimulated by treating the permeabilized cells with GTP-gamma S, and, significantly, the stimulatory effect is eliminated by a mutation in CDC42, a gene that encodes a Rho-like GTP-binding protein required for bud formation. Furthermore, the lack of actin nucleation activity in the cdc42 mutant can be complemented in vitro by a constitutively active Cdc42 protein. These results suggest that Cdc42 is closely involved in regulating actin assembly during polarized cell growth.